Ferrite composition, preparation method thereof and electronic equipment

By preparing ferrite compositions with specific components and proportions, the shortcomings of existing materials in mechanical strength and magnetic flux balance are solved, and high-performance ferrite materials are realized, suitable for thinning and diversified applications of electronic equipment. .

CN119409492APending Publication Date: 2025-02-11SHENZHEN SUNLORD ELECTRONICS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411568887.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing ferrite compositions are difficult to balance between mechanical strength and protective magnetic flux, making it difficult to meet the needs of lightweight and functional diversity when used in electronic devices.

Method used

By preparing a ferrite composition containing components such as Fe2O3, ZnO, CuO, NiO, MoO3 and Cr2O3, the component ratio and crystal particle size thereof are controlled to improve the saturation magnetic induction strength and mechanical properties of the material.

Benefits of technology

The high saturation magnetic induction strength and mechanical properties of the ferrite composition are achieved, and the thinning and functional diversified needs of electronic equipment are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of ferrite, and discloses a ferrite composition and a preparation method thereof, and electronic equipment, the ferrite composition comprises main components, the main components comprise, by mass, 39.5 wt%-73.5 wt% of Fe2O3, 12.2 wt%-16.5 wt% of ZnO, 3.1 wt%-5.2 wt% of CuO, and 7.8 wt%-11.2 wt% of NiO; the ferrite composition further comprises auxiliary components, and the auxiliary components comprise the following components in percentage by mass of the main components: 0.02 wt%-0.20 wt% of MoO3 and 0.02 wt%-0.20 wt% of Cr2O3. The ferrite composition has relatively high saturation flux density and mechanical properties, and can meet the requirements of lightening, thinning and functional diversification of the existing electronic equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ferrites, and in particular to a ferrite composition and a preparation method thereof, and electronic equipment. Background Art

[0002] Ferrite compositions mainly include two series: manganese-zinc ferrite compositions and nickel-zinc ferrite compositions. They are usually used in fields such as computers, communications, power supplies and consumer electronic devices, and are basic functional materials for the electronics industry.

[0003] There is a certain mutual restriction between the mechanical strength and protective magnetic flux of the existing ferrite composition, which is difficult to balance, so the performance of the inductor made of the ferrite composition is limited. Therefore, when it is applied to electronic equipment, it is difficult to meet the needs of electronic equipment for thinness and diversification of functions. Summary of the invention

[0004] The embodiment of the invention discloses a ferrite composition and a preparation method thereof, and an electronic device. The ferrite composition has high saturation magnetic induction intensity and mechanical properties, and can meet the requirements of existing electronic devices for thinness and lightness and diversified functions.

[0005] In a first aspect, an embodiment of the present application discloses a ferrite composition, wherein the ferrite composition comprises a main component, and the main component comprises, by mass percentage: Fe2O3 69.5wt% to 73.5wt%, ZnO 12.2wt% to 16.5wt%, CuO 3.1wt% to 5.2wt%, NiO 7.8wt% to 11.2wt%;

[0006] The ferrite composition further comprises auxiliary components, which, in terms of mass percentage of the main component, comprise: MoO3 0.02wt% to 0.20wt% and Cr2O3 0.02wt% to 0.20wt%.

[0007] Furthermore, the auxiliary component further comprises at least one of SnO2 0.01wt% to 0.30wt% and TiO2 0.02wt% to 0.20wt% in terms of mass percentage of the main component.

[0008] Furthermore, the average particle size of the crystals in the ferrite composition is 1.0 μm to 3.0 μm.

[0009] Furthermore, the density of the ferrite composition is 5.05 g / cm 3 ~5.15g / cm 3 .

[0010] In a second aspect, an embodiment of the present application discloses a method for preparing the ferrite composition according to any one of the first aspects, the preparation method comprising:

[0011] The main component raw materials are mixed and pre-sintered to obtain the main component; wherein, in terms of mass percentage, the main component raw materials include 69.5wt% to 73.5wt% of Fe2O3, 12.2wt% to 16.5wt% of ZnO, 3.1wt% to 5.2wt% of CuO, and 7.8wt% to 11.2wt% of NiO;

[0012] The auxiliary component raw materials are added to the main component and then granulated and sintered to obtain the ferrite composition; wherein, in terms of mass percentage of the main component, the auxiliary component raw materials include: MoO3 0.02wt% to 0.20wt% and Cr2O3 0.02wt% to 0.20wt%.

[0013] Furthermore, in the step of pre-sintering after mixing the main component raw materials, the pre-sintering temperature is 780° C. to 880° C., and the pre-sintering time is 2 h to 3 h.

[0014] Furthermore, in the step of adding the auxiliary component raw material into the main component for granulation and sintering, the sintering temperature is 1020° C. to 1150° C., and the sintering time is 2 h to 4 h.

[0015] Furthermore, in the step of adding the auxiliary component raw material to the main component for granulation and sintering, the granulation method is: after mixing the binder, the auxiliary component raw material and the main component, the extrusion granulation is performed, wherein the content of the binder is 1.5wt% to 2.0wt% as a percentage of the sum of the mass of the main component and the auxiliary component raw material.

[0016] Furthermore, before the step of pre-sintering the main component raw materials after mixing, the preparation method further comprises: grinding the main component raw materials after mixing, the grinding time being 3h to 4h; and / or,

[0017] After the step of pre-sintering the main component raw materials after mixing, and before the step of adding the auxiliary component raw materials into the main component for granulation and sintering, the preparation method further comprises: secondary grinding of the auxiliary component raw materials and the main component after mixing, and the grinding time is 4h to 6h.

[0018] In a third aspect, an embodiment of the present application discloses an electronic device, comprising the ferrite composition of any one of the first aspect, or the ferrite composition prepared by the preparation method of any one of the second aspect.

[0019] Compared with the prior art, the beneficial effects of this application are:

[0020] An embodiment of the present application provides a ferrite composition, which includes a main component and an auxiliary component, and the main component includes 69.5wt% to 73.5wt% of Fe2O3, 12.2wt% to 16.5wt% of ZnO, 3.1wt% to 5.2wt% of CuO, and 7.8wt% to 11.2wt% of NiO, and the auxiliary components include: 0.02wt% to 0.20wt% of MoO3 and 0.02wt% to 0.20wt% of Cr2O3. By controlling the content of the main component and the auxiliary component and adjusting the occupancy of the atomic structure, a higher atomic magnetic moment is obtained, which helps to improve the saturation magnetic induction intensity of the ferrite composition; in addition, the crystals in the ferrite composition are tightly fused, the structure is highly dense, and the mechanical properties are relatively high, which can meet the requirements of small and thin electronic devices with diversified functions.

[0021] Among them, the Fe2O3 content in the present application is relatively high, which helps to produce more magnetic phases, improve the temperature stability of the magnetic permeability of the ferrite composition, improve the magnetic properties of the ferrite composition, and further control the ratio of other components to help further improve the magnetic effect and mechanical strength of the material. Specifically, under the action of MoO3 and CuO, it helps to reduce the sintering temperature of the ferrite composition and limit the transition growth of the crystal, and further controlling the content of ZnO and Cr2O3 can change the lattice constant, thereby limiting the growth of the crystal, making the grain size smaller and more uniform, reducing the defects of the ferrite composition, and improving its structural stability. In addition, controlling the content of MoO3 and Cr2O3 within the scope of the present application can also improve the microstructure of the ferrite composition, reduce the porosity, make the fusion tightness between the crystals in the ferrite composition high, improve the compactness of the material, thereby helping to improve the mechanical properties and structural stability of the ferrite composition. In addition, controlling the contents of NiO, ZnO and MoO3 can also help improve the magnetic permeability of the ferrite composition, thereby further increasing the magnetic flux of the ferrite composition and reducing by-products in the ferrite composition, thereby improving the performance of the ferrite composition. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] In the present invention, the directions or positional relationships indicated by terms such as "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.

[0024] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those skilled in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0025] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0026] The technical solution provided by the present invention will be further described below in conjunction with embodiments.

[0027] Ferrite compositions mainly include two series: manganese-zinc ferrite compositions and nickel-zinc ferrite compositions. They are usually used in the fields of computers, communications, power supplies, and consumer electronics, and are basic functional materials for the electronics industry. Compared with manganese-zinc ferrite compositions, nickel-zinc ferrite compositions have the characteristics of high resistivity and high frequency of use, and are suitable for making magnetic core components of various sizes and shapes.

[0028] As electronic devices become smaller and thinner, the ferrite composite inductors used also need to become smaller and thinner, which requires the ferrite composite to have higher mechanical strength. In addition, as the functions of electronic devices become more and more diverse, the requirements for the rated current of inductors are also getting higher and higher, which requires the ferrite composite to have higher saturation magnetic induction.

[0029] However, there is a certain mutual restriction between the mechanical strength and the saturation magnetic induction intensity of the existing ferrite composition, which makes it difficult to meet the development trend of existing electronic equipment, resulting in the performance of the electronic equipment being affected.

[0030] Based on the above problems, an embodiment of the present application provides a ferrite composition, which not only has a high saturation magnetic induction intensity, but also has high mechanical properties, so that it can meet the development trend of small, light and thin electronic devices with diversified functions.

[0031] In a first aspect, an embodiment of the present application discloses a ferrite composition, the ferrite composition comprising a main component, in terms of mass percentage, the main component comprising: Fe2O3 69.5wt% to 73.5wt%, ZnO12.2wt% to 16.5wt%, CuO 3.1wt% to 5.2wt%, NiO 7.8wt% to 11.2wt%;

[0032] The ferrite composition further comprises auxiliary components, which, in terms of mass percentage to the main component, comprise: 0.02wt% to 0.20wt% of MoO3 and 0.02wt% to 0.20wt% of Cr2O3.

[0033] An embodiment of the present application provides a ferrite composition, which includes a main component containing 69.5wt% to 73.5wt% of Fe2O3, 12.2wt% to 16.5wt% of ZnO, 3.1wt% to 5.2wt% of CuO, and 7.8wt% to 11.2wt% of NiO, and an auxiliary component containing 0.02wt% to 0.20wt% of MoO3 and 0.02wt% to 0.20wt% of Cr2O3. By controlling the content of the main component and the auxiliary component, it is helpful to adjust the atomic structure and obtain a higher atomic magnetic moment, thereby improving the saturation magnetic induction intensity (Bs) of the ferrite composition; in addition, the crystals in the ferrite composition have a high degree of fusion tightness, a high structural density, and high mechanical properties, so that it can meet the requirements of small and thin electronic devices with diversified functions.

[0034] Among them, the main component of the present application has a high content of Fe2O3, so it promotes the ferrite composition to produce more magnetic phases, which helps to increase the Curie temperature of the ferrite composition. The higher Curie temperature allows the ferrite composition to still maintain ferromagnetism at a higher temperature, ensuring the temperature stability of the magnetic permeability of the ferrite composition and improving the magnetic properties of the ferrite composition. However, a high content of Fe2O3 will have an adverse effect on the crystal growth process of the ferrite composition, hinder the normal growth of the crystal, make the uniformity of the crystal size poor, and have more defects, and will also increase the porosity of the ferrite composition, making the ferrite composition less compact and less mechanically strong, and may also react with other components to form some non-ferrite phases, thereby adversely affecting the performance of the ferrite composition. Therefore, the present application helps to further improve the magnetic effect and mechanical strength of the material by further controlling the ratio of other components.

[0035] Specifically, the synergistic effect of MoO3 and CuO can help reduce the sintering temperature of the ferrite composition and avoid the transition growth of crystals, and further controlling the content of ZnO and Cr2O3 can change the lattice constant, thereby limiting the growth of crystals, making the size of the crystals smaller and more uniform, helping to reduce crystal defects and improve the structural stability and magnetic properties of the ferrite composition. In addition, controlling the content of MoO3 and Cr2O3 within the scope of this application can also improve the microstructure of the ferrite composition, reduce the porosity, make the crystals in the ferrite composition have high fusion tightness, improve the compactness of the material, and thus help improve the mechanical properties and structural stability of the ferrite composition. In addition, controlling the content of NiO, ZnO and MoO3 can also help improve the magnetic permeability of the ferrite composition, further improve the magnetic flux of the ferrite composition, reduce the by-products in the ferrite composition, and thus improve the performance of the ferrite composition.

[0036] Furthermore, the auxiliary components include at least one of 0.01wt% to 0.30wt% SnO2 and 0.02wt% to 0.20wt% TiO2.

[0037] In a first optional embodiment, the auxiliary components include SnO2, MoO3 and Cr2O3; in a second optional embodiment, the auxiliary components include TiO2, MoO3 and Cr2O3; in a third optional embodiment, the auxiliary components include SnO2, TiO2, MoO3 and Cr2O3, and the third optional embodiment is a preferred option.

[0038] Among them, the presence of SnO2 helps to reduce the anisotropy constant, reduce the magnetic moment ratio, increase the coercive force, and improve the performance of the ferrite composition. The introduction of TiO2 can increase the lattice constant, improve the DC resistivity, reduce the eddy current loss, reduce the Curie temperature, and increase the saturation magnetic induction intensity. And when the auxiliary components contain both substances, it helps to further increase the performance of the ferrite composition.

[0039] Furthermore, the average particle size of the crystals in the ferrite composition is 1.0 μm to 3.0 μm.

[0040] When the particle size is within the above range, the surface effect of the ferrite composition is enhanced, the magnetic domain structure and the arrangement of the magnetic moment are more easily affected, which helps to increase the coercive force of the material and improve the magnetic effect of the ferrite composition. In addition, it helps to improve the compactness of the ferrite composition, reduce the pores and defects of the ferrite composition, thereby improving the mechanical strength and structural stability of the ferrite composition. Among them, the particle size of the crystals in the ferrite composition can be measured by scanning electron microscopy. This application does not limit the measurement method of the average particle size of the crystals in the ferrite composition, as long as the purpose of this application can be achieved.

[0041] Furthermore, the density of the ferrite composition is 5.05 g / cm 3 ~5.15g / cm 3 .

[0042] Among them, the Archimedean principle can be used, that is, the buoyancy of an object in a liquid is equal to the weight of the liquid it displaces. By measuring the mass of the ferrite composition in air and the mass in water, the buoyancy of the ferrite composition is calculated based on the difference between the two, and then the volume of the ferrite composition is obtained, and then combined with its mass in air, the density is finally calculated.

[0043] When the density of the ferrite composition is within the above range, it indicates that the molecular structure is more compact and the bonding is more solid. The ferrite composition has higher mechanical properties. The higher density makes the arrangement of magnetic particles inside the ferrite composition denser and the interaction stronger, which helps to further improve the saturation magnetic induction intensity of the ferrite composition.

[0044] In a second aspect, the present application discloses a method for preparing the ferrite composition of the first aspect, the preparation method comprising:

[0045] The main component raw materials are mixed and pre-sintered to obtain the main component; wherein, in terms of mass percentage, the main component raw materials include 69.5wt% to 73.5wt% of Fe2O3, 12.2wt% to 16.5wt% of ZnO, 3.1wt% to 5.2wt% of CuO, and 7.8wt% to 11.2wt% of NiO;

[0046] The auxiliary component raw materials are added to the main component and then granulated and sintered to obtain a ferrite composition; wherein, in terms of mass percentage of the main component, the auxiliary component raw materials include: MoO3 0.02wt% to 0.20wt% and Cr2O3 0.02wt% to 0.20wt%.

[0047] Among them, the pre-sintering step allows the main component raw materials in the ferrite composition to be evenly mixed, and helps the main component raw materials to undergo preliminary crystallization, providing a starting crystal framework for the subsequent sintering step. The sintering step allows the auxiliary component raw materials to be evenly diffused into the main component, ensuring the sufficiency of the reaction between the auxiliary component raw materials and the main component, which helps to further adjust the crystal growth process, so that the prepared ferrite composition has higher particle uniformity and smaller particle size, which helps to improve the mechanical and magnetic properties of the ferrite composition.

[0048] Furthermore, in the step of pre-sintering after mixing the main component raw materials, the pre-sintering temperature is 780° C. to 880° C., and the pre-sintering time is 2 h to 3 h.

[0049] By setting the pre-sintering parameters within the above range, the main component raw materials are mixed evenly, which promotes their initial crystallization and makes the performance of the formed crystal framework better, which helps to ensure that the crystals of the prepared ferrite composition have higher quality.

[0050] Furthermore, the auxiliary component raw material is added to the main component to carry out granulation and sintering steps, the sintering temperature is 1020° C. to 1150° C., and the sintering time is 2 h to 4 h.

[0051] By setting the sintering parameters within the above range, the auxiliary component raw materials can be fully mixed in the main component, the mixing uniformity of the two is higher, and the reaction is more complete, which helps to ensure the uniformity of crystal growth and effectively improve the performance of the ferrite composition.

[0052] Furthermore, the auxiliary component raw material is added to the main component for granulation and sintering. The granulation method is: the binder, the auxiliary component raw material and the main component are mixed and then extruded and granulated, wherein the content of the binder is 1.5wt% to 2.0wt% as a percentage of the sum of the mass of the main component and the auxiliary component raw material.

[0053] When the content of the binder is within the above range, it helps to reduce the difficulty of extrusion granulation, and makes the bonding effect between materials higher, the contact tightness of the particles is good, which helps to improve the strength of the material, improves the structural stability of the material, and helps to avoid the influence of subsequent sintering steps on material deformation, thereby ensuring that the prepared ferrite composition has high structural stability.

[0054] Furthermore, before the step of pre-sintering the main component raw materials after mixing, the preparation method further comprises: grinding the main component raw materials after mixing, the grinding time being 3h to 4h; and / or,

[0055] After the step of pre-sintering the main component raw materials after mixing, and before the step of adding the auxiliary component raw materials into the main component for granulation and sintering, the preparation method further includes: secondary grinding of the auxiliary component raw materials and the main component after mixing, and the grinding time is 4h to 6h.

[0056] The primary grinding allows the main raw materials to be mixed more uniformly, which helps facilitate the mutual reaction between the components in the subsequent pre-sintering step, ensures that the formed crystal skeleton has higher performance, and reduces the generation of by-products. The secondary grinding step allows the main and auxiliary raw materials to be mixed more fully, which helps facilitate the subsequent granulation and sintering steps, thereby making the sintered ferrite composition more dense and having better performance. With the synergistic effect of the two, the crystal quality of the ferrite composition can be effectively improved, ensuring that its particle size is small and its uniformity is high, which helps to improve its performance.

[0057] In a third aspect, an embodiment of the present application discloses an electronic device, which includes the ferrite composition of the first aspect, or the ferrite composition prepared by the preparation method of the second aspect.

[0058] The technical solution of the present application will be further explained below in conjunction with more specific embodiments and experimental test results.

[0059] Embodiment 1:

[0060] The present application provides a method for preparing a ferrite composition, the preparation method comprising:

[0061] The main component raw materials are mixed and ground once for 3.5 hours, wherein the main component raw materials include 70.5wt% Fe2O3, 14.7wt% ZnO, 4.1wt% CuO, and 10.7wt% NiO by mass fraction;

[0062] The mixed main component raw materials are pre-sintered to obtain the main component, wherein the pre-sintering temperature is 820° C. and the time is 2.5 h;

[0063] The auxiliary component raw material and the main component are mixed and then ground twice for 5 hours, wherein the auxiliary component includes 0.05wt% MoO3, 0.02wt% SnO2, 0.03wt% Cr2O3, and 0.03wt% TiO2 in terms of mass percentage of the main component;

[0064] The binder, the auxiliary component raw material and the main component are mixed and then extruded and granulated, and the granulated material is pressed into a blank, wherein the binder content is 1.7wt% based on the percentage of the sum of the weight of the auxiliary component raw material and the main component;

[0065] The blank was placed in a box-type sintering furnace for sintering to obtain a ferrite composition, wherein the sintering temperature was 1110°C, the sintering time was 3 hours, the average particle size of the crystals in the ferrite composition was 2 μm, and the density of the ferrite composition was 5.09 g / cm 3 .

[0066] The difference between Example 2, Example 3, Comparative Example 3 and Comparative Example 4 and Example 1 is only the main component raw material.

[0067] The difference between Example 4 and Comparative Examples 5 to 8 and Example 1 is only the auxiliary component raw materials.

[0068] Embodiment five:

[0069] The only difference between this embodiment and the first embodiment is that the average grain size of the crystals in the ferrite composition of this embodiment is 5 μm.

[0070] Embodiment six:

[0071] The difference between this embodiment and the first embodiment is that the density of the ferrite composition of this embodiment is 6.15 g / cm 3 .

[0072] The difference between Comparative Example 1 and Comparative Example 2 and Example 1 is only the main component raw material and the auxiliary component raw material.

[0073] The parameter change details of Examples 1 to 4 and Comparative Examples 1 to 8 are shown in Table 1.

[0074] Table 1 Summary of main ingredients and auxiliary ingredients of Examples and Comparative Examples

[0075]

[0076] Note: In Table 1, “ / ” indicates that there is no related prepared substance.

[0077] Performance Test:

[0078] Magnetic permeability: The magnetic induction intensity and magnetic field intensity of the material are tested in a static magnetic field to calculate the magnetic permeability.

[0079] Quality Factor: By measuring the ratio of the resonant voltage to the input voltage, the quality factor value can be displayed directly on the output instrument.

[0080] Saturation flux density: By applying an alternating magnetic field, the magnetic material is continuously magnetized and demagnetized, and the highest point of the magnetization curve is measured, which is the saturation flux density.

[0081] Compressive Strength Test: A common method for determining the compressive strength of individual carrier particles. Using a device with a horizontal plate that moves up and down, the sample particles are loaded with increasing amounts of force until the sample breaks and the crushing load is recorded.

[0082] Table 2 Performance test results of ferrite compositions

[0083]

[0084] Analysis of the data of Examples 1 to 6 and Comparative Examples 1 and 2 shows that the performance of the examples is better than that of Comparative Examples 1 and 2. This is because the ferrite compositions of the examples all contain auxiliary component raw materials. The presence of the auxiliary component raw materials helps to improve the crystallization process in only one step and adjust the occupancy of the atomic structure, so that the crystals in the ferrite composition are tightly fused and the structure is highly dense, thereby helping to improve the mechanical properties and saturation magnetic induction intensity of the ferrite composition.

[0085] Analysis of the data of Example 1, Comparative Example 3 and Comparative Example 4 shows that the performance of Example 1 is better than that of Comparative Example 3. This is because the Fe2O3 content in Example 1 is relatively high, which helps to produce more magnetic phases, thereby helping to improve the magnetic properties of the ferrite composition; the performance of Example 1 is better than that of Comparative Example 4. This is because the Fe2O3 content in Example 1 is relatively low, and its matching degree with other raw materials is higher, thereby ensuring that the quality of the prepared crystal is relatively high, thereby helping to improve the performance of the ferrite composition.

[0086] Analysis of the data of Example 1 and Comparative Examples 5 to 8 shows that the performance of Example 1 is better than that of Comparative Examples 5 to 7. This is because the auxiliary component raw materials in the examples contain MoO3 Cr2O3, which helps to improve the sintering temperature of the ferrite composition, avoid excessive growth of crystals, and limit the growth of crystals, so that the prepared ferrite composition has fewer defects, high structural density, and good magnetic properties. Analysis of the data of Example 1 and Comparative Example 8 shows that the performance of Example 1 is better than that of Comparative Example 8. This is because the contents of MoO3 and Cr2O3 in Example 1 are both within the scope of the present application, so they have a high degree of matching with other raw materials, so that the prepared crystals are of higher quality and the performance of the ferrite composition is better.

[0087] Analysis of the data of Example 1 and Example 3 shows that Example 1 has the best performance, indicating that the main component raw material and the auxiliary component raw material have a high degree of matching, which helps to reduce the production of by-products and improve the crystallization quality of the crystal, thereby improving the performance of the ferrite composition to a high degree.

[0088] Analysis of the data of Example 1 and Example 4 shows that Example 1 has the best performance. This is because the auxiliary component formula in Example 1 also contains SnO2 and TiO2, which helps to reduce the anisotropy constant, reduce the magnetic moment ratio, increase the coercive force, increase the lattice constant, reduce eddy current loss, reduce the Curie temperature, and increase the saturation magnetic induction intensity.

[0089] Analysis of the data of Example 1 and Example 5 shows that Example 1 has the best performance. This is because the average particle size of the crystals in the ferrite composition in Example 1 is smaller, and the formed ferrite composition has higher structural density and better stability.

[0090] Analysis of the data of Example 1 and Example 6 shows that Example 1 has the best performance. This is because the density of the ferrite composition of Example 1 is relatively small, indicating that the crystal force inside the material is appropriate, avoiding the problem of restricted movement of magnetic domains due to high crystal interaction, thereby reducing the magnetic permeability.

[0091] The ferrite composition, preparation method thereof, and electronic device disclosed in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the ferrite composition, preparation method thereof, and electronic device. At the same time, for those skilled in the art, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A ferrite composition, characterized in that: The ferrite composition includes main components, which include, by mass percentage, 69.5wt% to 73.5wt% of Fe2O3, 12.2wt% to 16.5wt% of ZnO, 3.1wt% to 5.2wt% of CuO, and 7.8wt% to 11.2wt% of NiO; The ferrite composition further comprises auxiliary components, which, in terms of mass percentage of the main component, comprise: MoO3 0.02wt% to 0.20wt% and Cr2O3 0.02wt% to 0.20wt%.

2. The ferrite composition according to claim 1, characterized in that Calculated by mass percentage of the main component, the auxiliary component further includes at least one of SnO2 0.01wt% to 0.30wt% and TiO2 0.02wt% to 0.20wt%.

3. The ferrite composition according to claim 1, characterized in that The average particle size of the crystals in the ferrite composition is 1.0 μm to 3.0 μm.

4. The ferrite composition according to claim 1, characterized in that The density of the ferrite composition is 5.05 g / cm 3 ~5.15g / cm 3 .

5. A method for preparing a ferrite composition according to any one of claims 1 to 4, characterized in that: The preparation method comprises: The main component raw materials are mixed and pre-sintered to obtain the main component; wherein, in terms of mass percentage, the main component raw materials include 69.5wt% to 73.5wt% of Fe2O3, 12.2wt% to 16.5wt% of ZnO, 3.1wt% to 5.2wt% of CuO, and 7.8wt% to 11.2wt% of NiO; The auxiliary component raw materials are added to the main component and then granulated and sintered to obtain the ferrite composition; wherein, in terms of mass percentage of the main component, the auxiliary component raw materials include: MoO3 0.02wt% ~ 0.20wt% and Cr2O3 0.02wt% ~ 0.20wt%.

6. The preparation method according to claim 5, characterized in that: In the step of pre-sintering after mixing the main component raw materials, the pre-sintering temperature is 780° C. to 880° C., and the pre-sintering time is 2 h to 3 h.

7. The preparation method according to claim 5, characterized in that: In the step of adding the auxiliary component raw material into the main component for granulation and sintering, the sintering temperature is 1020° C. to 1150° C. and the sintering time is 2 h to 4 h.

8. The preparation method according to claim 5, characterized in that: In the step of adding the auxiliary component raw material to the main component for granulation and sintering, the granulation method is: after mixing the binder, the auxiliary component raw material and the main component, the mixture is extruded and granulated, wherein the content of the binder is 1.5wt% to 2.0wt% as a percentage of the sum of the mass of the main component and the auxiliary component raw material.

9. The preparation method according to claim 5, characterized in that: Before the step of pre-sintering the main component raw materials after mixing, the preparation method further comprises: grinding the main component raw materials once after mixing, the grinding time being 3h to 4h; and / or, After the step of pre-sintering the main component raw materials after mixing, and before the step of adding the auxiliary component raw materials into the main component for granulation and sintering, the preparation method further comprises: secondary grinding of the auxiliary component raw materials and the main component after mixing, and the grinding time is 4h to 6h.

10. An electronic device, characterized in that: The electronic device comprises the ferrite composition according to any one of claims 1 to 4, or the ferrite composition prepared by the preparation method according to any one of claims 5 to 9.

Citation Information

Patent Citations

  • NiZn series ferrite material and preparing method thereof

    CN101256865A

  • High-Bs high-strength soft magnetic ferrite material and preparation method thereof

    CN106995311A

  • Wide temperature rang, low temperature coefficient, high magnetic permeability NiZn ferrite material and its preparing method

    CN1858020A

  • Method for manufacturing dry mold sintered magnet

    JP2002305106A